Perception of Healthcare Providers About the Use of Social Media to Manage a Healthy Diet in Saudi Arabia - Alanzi, Turki; Altuwailib, Maryam; Saadah, Amjad Mohammed; Alanezi, Fahad (Frontiers in Public Health, 2021)
Purpose: The objective of this study was to investigate the perception of healthcare providers about the use of social media to manage a healthy diet in Saudi Arabia. Participants and methods: A cross-sectional study was designed to investigate the use of social media to manage a healthy diet. The sample was constituted by 308 healthcare professionals from Saudi Arabia. The response was 50.61% and WhatsApp was employed to distribute the questionnaire. Results: 55% of the participants were under 30 years of age, and 71% were females. 55% of the participants had a bachelor's degree, 66% used social networks more than 4 hours a day, and 78% utilized social media to get information about a healthy diet. The respondents employed the following platforms for this purpose: Instagram (27%), YouTube (19%), Snapchat (19%), WhatsApp (18%), Twitter (8%) and Facebook (5%). The respondents considered that social media were very helpful to educate (44%), communicate with specialists (33%) and get applications for a healthy diet (38%). They thought that social media were very helpful to improve knowledge about a healthy diet (47%), diet awareness (42%), diet outcomes (37%) and lifestyle (37%). Conclusion: According to the perception of health providers, social media can be used to manage a healthy diet in Saudi Arabia. Also, the growing use of social media in this country represents the potential to create programs that encourage and promote healthy eating habits in the Kingdom. Instagram, YouTube, Snapchat and WhatsApp platforms can be used for this purpose.